â€œMOPHETHâ€ - TINDAKAN PROFETIS MAKNA SIMBOLIS Dan Relevansinya Bagi Gereja Masa Kini - Gunawan, Yehuda Indra; Pakiding, Herman (Sekolah Tinggi Teologi Kristus Alfa Omega, 2020)
Symbolic prophetic action is one method of delivering God's message to His people by means of the prophet. It can be used as a social and theological criticism, which brings a good change in Israelitesâ€™ life. Hoped that this research can answer the question which is relevant to the symbolic prophetic action carried out by the Old Testament prophets for the church today. Socio-religious questions used to describe classical to modern social theories. The